Paradigma Pemikiran Simbiotik dalam Fikih Siyasah Kontemporer - Yusuf, Aida; Rahayuningsih, Citra Dwi; Islamy, Nor; Sukti , Surya (Jejak digital: Jurnal Ilmiah Multidisiplin, 2026)
The symbiotic-mutualistic paradigm is a moderate approach in understanding the relationship between religion and the state, which has long been debated in Islamic social and political thought. It serves as a middle path between the integralistic approach that fully unites religion and state and the secularistic approach that strictly separates them. This paper aims to explain the concept, historical development, characteristics, and relevance of the symbiotic-mutualistic paradigm in national and state life. The research applies a library research method using a descriptive analysis of relevant literature. The findings indicate that this paradigm positions religion as a source of moral values and the state as a regulator of public affairs, both functioning in a complementary and mutually reinforcing relationship. In the Indonesian context, founded upon Pancasila, this paradigm is considered relevant as it accommodates religious values without establishing a religious state. Therefore, the symbiotic-mutualistic paradigm offers a moderate, inclusive, and harmonious framework for governance and national life.